The Competition for Cumania between Hungary and Bulgaria (1211–1247) - Madgearu, Alexandru (Studia Ceranea, 2022)
Because the alliance between the Cumans and Bulgaria was a danger both for Hungary and the Latin Empire, it was preferable for Hungary to extend its domination over Cumania. The Teutonic knights were settled in south-eastern Transylvania in 1211 to defend it against the Cumans, who, after 1214, became enemies also for Bulgaria. Besides the few fortresses built in the Bârsa land, there is no certain proof for an expansion of the Teutonic Order outside the Carpathians, and by consecquence of the Hungarian kingdom, in the period before the Mongol invasion of 1241. After the departure of the Teutonic knights in 1225, Cumania became the target of the Dominican mission which was present since around 1221 in Terra Severin, a north-Danubian Bulgarian possession. The Cuman bishopric was established in 1227. The subjection of these Cumans made useless the preservation of the Hungarian-Bulgarian alliance closed in 1214, and the consequence was the annexation of Terra Severin by Hungary, sometimes between 1228 and 1232, as a Banat. The final act of the Hungarian expansion in Cumania was the introduction of the title of King of Cumania by Bela IV in 1236. The region where it was established the bishopric of Cumania continued to be under the influence of the Church of Tărnovo, even after the end of the domination of the Bulgarian state in this north-Danubian territory. In 1241, the Cuman bishopric was destroyed by the Mongol invasion. Because the Golden Horde domination did not extend west of Olt in the first years after 1242, Bela IV tried to regain positions by summoning the Hospitaller Knights in 1247. Terra Severin remained a part of the Hungarian kingdom, but the function of Ban was abandoned or suspended. One mission of the Hospitallers was to extend the Hungarian domination in Cumania, in the regions which were then conquered by the Mongols. The Mongol domination prevented the emergence of a Cuman kingdom in Moldavia, vassal of Hungary. Only the decline of the Golden Horde made possible a new penetration of the Hungarian kingdom in the former Cumania, in 1345. The former Cumania entered in the new states created during the 14th century by the Romanians liberated from the Hungarian domination, Wallachia and Moldavia.